PENGARUH SISTEM SELEKSI, PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - CLARISA, REBEKHA; GULO, YUPITER (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to analyze and determine the influence of system selection, training, and job satisfaction on the employee performance of PT X. Sampling using non-probability sampling technique with a total sample used as many as 145 respondents. Data collection was carried out by distributing questionnaires to all respondents. The method of data analysis in this study is using multiple linear regression. Prior to testing the hypothesis, data were analyzed using research instrument testing, classical assumption testing and model testing using statistical software program. The results of this study indicate that system selection and job satisfaction has an effect on employee performance. Meanwhile, Training has no effect on employee performance